Islamophobia and Social Conflicts in West Borneo - Amelyadi; Suryadi; Sumin; Suryadi, Suryadi (Universitas Muhammadiyah Makassar, 2025)
This study explores the phenomenon of Islamophobia and negative stereotypes toward Islam in West Borneo, Indonesia, using a phenomenological and qualitative approach. Informants included religious leaders, community leaders, and non-Muslim students. Data were gathered through in-depth interviews and analyzed using content analysis. Findings reveal that Islamophobia in West Borneo is a real, though subtle, issue that has yet to significantly disrupt social life. Contributing factors include limited understanding of Islam, persistent negative stereotypes, and biased media coverage. Addressing this issue requires a collaborative effort involving government, communities, media, and educational institutions. Effective strategies include inclusive education, interfaith dialogue, accurate media representation, inter-community cooperation, and supportive public policy promoting tolerance and diversity. While this study is limited in scope, it highlights the presence of Islamophobia and its potential to influence social dynamics. Recognizing that the severity and prevalence of Islamophobia may vary by region, further comprehensive and contextual research is essential to fully understand and mitigate its impact in West Borneo and beyond. Keywords : : Islamophobia; Social Conflict; Negative Stereotypes.